OQSAROY COMPLEX: A MODERN ARCHITECTURAL MARVEL COMBINING TRADITION AND INNOVATION (Нововведения Cовременного Научного Развития в Эпоху Глобализации: Проблемы и Решения, 2023)
The Oqsaroy Complex is an architectural masterpiece that beautifully blends traditional design elements with innovative technologies, representing a harmonious fusion of the past and the present. Situated in the heart of Uzbekistan, this complex showcases the rich cultural heritage of the region while embracing modern advancements in construction and sustainable practices.